2022
DOI: 10.1029/2021gl097699
|View full text |Cite
|
Sign up to set email alerts
|

The 2021 Pacific Northwest Heat Wave and Associated Blocking: Meteorology and the Role of an Upstream Cyclone as a Diabatic Source of Wave Activity

Abstract: The heat wave that enveloped the Pacific Northwest from late June through early July 2021 delivered unprecedented temperatures to the normally cool region -108°F (42°C) in Seattle, 116°F (47°C) in Portland -and claimed over 1,000 lives mostly in British Columbia (AON, 2021). One preliminary study puts it in a 1-in-1,000 years event category (Philip et al., 2021). As with most heat waves in the midlatitudes (Fang & Lu, 2020;Pfahl & Wernli, 2012), the event was associated with an anomalous behavior of the jet st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 29 publications
(66 reference statements)
10
42
0
Order By: Relevance
“…Fitting a Theil-Sen regression model, we demonstrate that the changes in the size and intensity of blocks scale well with the increase in latent heating, especially for winter blocks over the oceans. This agrees with previous work that demonstrated the causal effect of latent heating on block intensity and size in numerical case study experiments (Croci-Maspoli et al 2007, Grams and Archambault 2016, Maddison et al 2020, Steinfeld et al 2020, Neal et al 2022.…”
Section: Discussionsupporting
confidence: 92%
“…Fitting a Theil-Sen regression model, we demonstrate that the changes in the size and intensity of blocks scale well with the increase in latent heating, especially for winter blocks over the oceans. This agrees with previous work that demonstrated the causal effect of latent heating on block intensity and size in numerical case study experiments (Croci-Maspoli et al 2007, Grams and Archambault 2016, Maddison et al 2020, Steinfeld et al 2020, Neal et al 2022.…”
Section: Discussionsupporting
confidence: 92%
“…Then, in a seamless transition as the air became engulfed in the anticyclone at a high altitude, subsidence and the associated adiabatic heating enabled a continuous conversion of potential into internal energy. Our findings confirm and expand on Neal et al (2022) who focused on the dynamical implications of upwind latent heating but suggested that the unusual tropospheric warmth in late June 2021 in the PNW originated in lower latitudes. The authors also reasoned that heat released from condensation may have contributed to the elevated temperatures in the troposphere, but did not calculate backward trajectories or perform any other detailed analyses.…”
Section: Unraveling the Role Of Upwind Latent Heatingsupporting
confidence: 90%
“…Even though hot events are exclusively diagnosed based on temperature here, many of them are associated with anticyclonic circulation aloft, which implies adiabatic warming due to subsidence particularly in the last 72 hr (Zschenderlein et al, 2020). While this adiabatic heating-converting potential into internal energy-is often considered to be a key driver of high near-surface temperatures in the midlatitudes (e.g., Bieli et al, 2015), it cannot explain the presence of high potential temperatures in the upper troposphere such as witnessed during the 2021 PNW heatwave (Neal et al, 2022). Therefore, to investigate the unprecedented free tropospheric heat during the 2021 PNW event, we consider the initial state of air 15 days prior to arriving, and processes occurring en route that shape the final state above the respective hot extreme.…”
Section: Diagnosis Of Latent Heating Along Trajectoriesmentioning
confidence: 94%
“…This perturbation seeded a Rossby wave train, which propagated eastward along a midlatitude wave guide, and modified the upper tropospheric winds associated with the wave guide as it progressed. By June 25th, an omega-block had developed over the PNW, which progressed eastward and intensified over the course of the heatwave (Neal et al, 2022;Philip et al, 2021). A cross-Pacific atmospheric river also transported latent heat into the region (Mo et al, 2022).…”
mentioning
confidence: 99%